Effects of household debt on economic growth in South Africa - Bwalya, Rachael Mulenga (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
South Africa's household debt relative to GDP has risen rapidly over the past decade. There is concern that high levels of household debt may decrease spending in the future and hence in the long run slow down economic growth. Thus, this study investigates the impact of household debt on growth in South Africa from 1987Q3 to 2022Q1. The research draws upon first-generation theories which include the absolute income hypothesis, life cycle hypothesis, and permanent income hypothesis, and second-generation theories which include the neo-Kaleckian model, the Super multiplier model, and the Steindl model. The impact of this relationship is assessed using a Vector Autoregressive (VAR) model, with a Toda-Yamamoto modification for some regressions. It is discovered that household debt has a positive short-term influence on economic growth, however, the influence is weak, and it decreases in the long run. Types of household debt such as credit card debt have shown to have a positive and strong influence on economic growth in South Africa from the short run to the long run, however, mortgage debt has shown weak positive influence on economic growth from the short 105 run to the long run. The study found that the growth maximizing ratios for household debt to 106 GDP ratio is 70 percent. The growth maximising credit card debt level is ZAR 72 403, in nominal terms and for mortgage debt is ZAR 5 980 000. The findings are expected to assist policymakers such as central banks and government authorities in formulating relevant policies to ensure economic sustainability through macro-prudential policy and strategies for household debt management.
Keywords: Household debt; Mortgage loans -- South Africa; Credit card debt; Gross domestic product -- South Africa; Economic growth